Forage grasses with lower uptake of caesium and strontium could provide ‘safer’ crops for radiologically contaminated areas - Penrose, Beth; Beresford, Nicholas A.; Crout, Neil M.J.; Lovatt, J. Alan; Thomson, Russell; Broadley, Martin R. (Public Library of Science, 2017)
Substitution of a species or cultivar with higher uptake of an element by one with lower uptake has been proposed as a remediation strategy following accidental releases of radioactivity. However, despite the importance of pasture systems for radiological dose, species/cultivar substitution has not been thoroughly investigated for forage grasses. 397 cultivars from four forage grass species; hybrid ryegrass (Lolium perenne L. x Lolium multiflorum Lam.), perennial ryegrass (Lolium perenne L.), Italian ryegrass (Lolium multiflorum Lam.) and tall fescue (Festuca arundinacea Shreb.); were sampled from 19 field-based breeding experiments in Aberystwyth and Edinburgh (UK) in spring 2013 and analysed for caesium (Cs) and strontium (Sr) concentrations. In order to calculate concentration ratios (CRs; the concentration of an element in a plant in relation to the concentration in the soil), soils from the experiments were also analysed to calculate extractable concentrations of Cs and Sr. To test if cultivars have consistently low Cs and Sr concentration ratios, 17 hybrid ryegrass cultivars were sampled from both sites again in summer 2013 and spring and summer 2014. Tall fescue cultivars had lower Cs and Sr CRs than the other species. Three of the selected 17 hybrid ryegrass cultivars had consistently low Cs CRs, two had consistently low Sr CRs and one had consistently low Cs and Sr CRs. Cultivar substitution could reduce Cs CRs by up to 14-fold and Sr CRs by 4-fold in hybrid ryegrass. The identification of species and cultivars with consistently low CRs suggests that species or cultivar substitution could be an effective remediation strategy for contaminated areas.